2006
DOI: 10.1002/app.23317
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and application of acrylonitrile‐grafted cyanoethyl cellulose for the removal of copper (II) ions

Abstract: Cyanoethyl cellulose (CE-Cell) with two different degrees of substitution of 0.37 and 0.60 were prepared from cotton linter. The ionic-xanthate method was used to graft the acrylonitrile onto CE-Cell to form acrylonitrile-grafted cyanoethyl cellulose (GCE-Cell). The conditions of grafting such as sodium hydroxide concentration, grafting time, monomer concentration, and temperature were optimized. The hydrolyzed CE-Cell and GCE-Cell were applied for the adsorption of copper (II) ions from aqueous solution. IR s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(38 citation statements)
references
References 19 publications
(15 reference statements)
0
35
0
2
Order By: Relevance
“…It was found that metal-ion removal depends on the protonation and deprotonation properties of acidic and basic groups, i.e. pH value of the medium [58].…”
Section: Tea Industry Wastementioning
confidence: 99%
“…It was found that metal-ion removal depends on the protonation and deprotonation properties of acidic and basic groups, i.e. pH value of the medium [58].…”
Section: Tea Industry Wastementioning
confidence: 99%
“…Cellulose has a low absorption capacity as well as variable physical stability. Therefore, chemical modification of cellulose can be carried out to achieve adequate structural durability and efficient liquid retention and adsorption capacity for liquid waste processing [4]. Chemical modification can be used to vary certain properties of cellulose such as its hydrophilic or hydrophobic character, elasticity, water sorbency, adsorptive or ion-exchange capability, resistance to microbiological attack and thermal resistance [5].…”
Section: Introductionmentioning
confidence: 99%
“…The NaSCNCs acts as nanoadsorbent in removing Pb 2+ and Cd 2+ , and it is able to regenerate with NaCl solution. These suggested that the chemically modified cellulose could potentially achieve efficient adsorption capacity of heavy metal ions as stated by [19]. The cellulose can adsorb metal ions via ion exchange which contributed from the active sites present on them.…”
Section: Cadmium Removalmentioning
confidence: 91%